Cooking up the Culinary Nation or Savoring its Regions? Teaching Food Studies in Vietnam. Issue 1 (31st May 2018) - Annear, Christopher; Harris, Jack
Abstract : "In food, as in death, we feel the essential brotherhood of man." Vietnamese Proverb This paper explores whether or not there is an identifiably Vietnamese national cuisine, one in which the ingredients, recipes, and/or dishes socially, culturally, and politically unite Vietnamese people. It contends that Vietnam, with its long history of foreign invaders, its own appropriation of the middle and southern regions, and its varied regional geographies, provides a critical example for Food Studies of the need to interrogate the idea of a national cuisine and to differentiate it from regional and local cuisines. The paper examines how cookbook authors and cooking schools have more generally sought to represent Vietnamese dishes as national, but that there is a strong argument against the claim of a Vietnamese national cuisine. We advocate a Food Studies methodology that creates an effective pedagogy that explores whether or not national populations are unified as single gastro-states or atomized by a plurality of regional cuisines. Through experiential assignments and student work we illustrate how Food Studies presents the pedagogical opportunity for students to study and learn at the intersection of national politics and the everyday lives of people, providing a framework for understanding connections of labor, gender, class, and, essentially, taste, among many other values. In the case of Vietnamese food, the critical details of ingredients, preparation, and consumption both reveal and conceal truths about the Vietnamese people.